GROUP DEVELOPMENT STAGES. A BRIEF COMPARATIVE ANALYSIS OF VARIOUS MODELS - Sebastian VAIDA; Dan ȘERBAN (Studia Universitatis Babes-Bolyai, 2021)
Group Development is one of the most important cornerstones of social life. It dictates how our work and social circles develop and influences the relationships in our lives, and in turn, these relationships dictate the levels of satisfaction we report in our lives. Teamwork is also important in our experiences as it is strongly related to group development and is linked with many aspects, such as professionalism and efficiency in teams. In this paper, we discuss the importance of group development for any forming teams and analyze the concept within nine models (Bass and Ryterband, Tubb, Cog's Ladder, Homan, Woodcock, Fisher, Jones, Tuckman and Wheelan), with a particular accent on the last two (Tuckman and Wheelan).